BOGASATSWANA: redbuilding the boat while sailing - Phetogo, Thebeyame (Michaelis School of Fine Art, 2020)
Bogasatswana: Rebuilding the Boat while Sailing, is an attempt to both transmit and disrupt a story-world whose make-up is based on my country of origin, Botswana. It is an exercise in worldbuilding through painting, wherein I establish post-colonial Botswana as a fictional place through the interrogation of gaps within the historicised national myths of the country and locate myself in said place and medium as a subject in the contemporary moment. Rather than the presentation of a fully realized fictional world, this project privileges the attempt at articulating a subjective world-version as informed by my positionality. As with solving a mathematical equation, I endeavour to show my working in the making visible of this space.